Innovative approaches for augmenting dielectric properties in cross-linked polyethylene (XLPE): a review - Nazrin, A.; Kuan, T. M.; Mansour, Diaa Eldin A.; A. Farade, Rizwan; Ariffin, A. Mohd; Rahman, M. S. Abd; Abdul Wahab, Noor Izzri (Elsevier, 2024)
Throughout the history of power systems, power cables have been used to securely and efficiently distribute electrical energy to the destined locations. Cross-linked polyethylene (XLPE), a commonly used insulator in high-voltage cables, have several desirable properties, such as low dielectric loss, high dielectric constant, high thermal conductivity, enhanced thermal stability, and superior resistance against electrical stress. However, further improvements of XLPE's performance are needed. The incorporation of large specific surface area nanoparticles, such as boron nitride nanosheets and graphene oxide, exhibited a great potential in enhancing XLPE's properties. These nanoparticles create numerous trapping sites, even at small loading levels, due to their large interfacial regions. In addition, voltage stabilisers with polar groups can scavenge high-energy electrons generated by local electric fields, thereby inhibiting the electrical tree growth. Another important aspect of enhancing XLPE's dielectric performance is the inclusion of antioxidants with phenolic groups. These antioxidants react with peroxyl radicals, mitigating their harmful effects. This review summarises the effects of nanoparticles, voltage stabilisers, antioxidants, and polymer amalgamation on dielectric performance of XLPE as an insulation material. The major challenges in dielectric insulation such as breakdown voltage strength, electrical tree growth, structural defect, space charge accumulation, and thermal aging are addressed.